Sustained Release of Prostaglandin E2 in Fibroblasts Expressing Ectopically Cyclooxygenase 2 Impairs P2Y-Dependent Ca2+-Mobilization - María Pimentel-Santillana; Paqui G. Través; Raquel Pérez-Sen; Esmerilda G. Delicado; Paloma Martín-Sanz; María Teresa Miras-Portugal; Lisardo Boscá (Mediators of Inflammation)
The nucleotide uridine trisphosphate (UTP) released to the extracellular milieu acts as a signaling molecule via activation of specific pyrimidine receptors (P2Y). P2Y receptors are G protein-coupled receptors expressed in many cell types. These receptors mediate several cell responses and they are involved in intracellular calcium mobilization. We investigated the role of the prostanoid PGE2 in P2Y signaling in mouse embryonic fibroblasts (MEFs), since these cells are involved in different ontogenic and physiopathological processes, among them is tissue repair following proinflammatory activation. Interestingly, Ca2+-mobilization induced by UTP-dependent P2Y activation was reduced by PGE2 when this prostanoid was produced by MEFs transfected with COX-2 or when PGE2 was added exogenously to the culture medium. This Ca2+-mobilization was important for the activation of different metabolic pathways in fibroblasts. Moreover, inhibition of COX-2 with selective coxibs prevented UTP-dependent P2Y activation in these cells. The inhibition of P2Y responses by PGE2 involves the activation of PKCs and PKD, a response that can be suppressed after pharmacological inhibition of these protein kinases. In addition to this, PGE2 reduces the fibroblast migration induced by P2Y-agonists such as UTP. Taken together, these data demonstrate that PGE2 is involved in the regulation of P2Y signaling in these cells.